Coordination of a remote mHealth infrastructure for atrial fibrillation management during COVID-19 and beyond: TeleCheck-AF. (September 2020) - van der Velden, Rachel MJ; Hermans, Astrid NL; Pluymaekers, Nikki AHA; Gawalko, Monica; Vorstermans, Bianca; Martens, Herm; Buskes, Saskia; Crijns, Harry JGM; Linz, Dominik; Hendriks, Jeroen M
During the coronavirus 2019 (COVID-19) pandemic, outpatient visits for patients with atrial fibrillation (AF), were converted into teleconsultations. As a response to this, a novel mobile health (mHealth) intervention was developed to support these teleconsultations with AF patients: TeleCheck-AF. This approach incorporates three fundamental components: 1) "Tele": A structured teleconsultation. 2) "Check": An app-based on-demand heart rate and rhythm monitoring infrastructure. 3) "AF": comprehensive AF management. This report highlights the significant importance of coordination of the TeleCheck-AF approach at multiple levels and underlines the importance of streamlining care processes provided by a multidisciplinary team, using an mHealth intervention, during the COVID-19 pandemic. Moreover, this report reflects on how the TeleCheck-AF approach has contributed to strengthening the health system in maintaining management of this prevalent sustained cardiac arrhythmia, whilst keeping patients out of hospital, during the pandemic and beyond.